Numerical analysis of the failure process of soil–rock mixtures through computed tomography and PFC3D models - Ju, Yang; Sun, Huafei; Xing, Mingxu; Wang, Xiaofei; Zheng, Jiangtao (International journal of coal science & technology, 2018)
Soil–rock mixture (SRM) is a unique type of geomaterial characterized by a heterogeneous composition and a complicated structure. It is intractable for the continuum-based soil and rock mechanics theories to accurately characterize and predict the SRM’s mechanical properties. This study reports a novel numerical method incorporating microfocus computed tomography and PFC3D codes to probe the deformation and failure processes of SRM. The three-dimensional (3D) PFC models that represent the SRM’s complex structures were built. By simulating the entire failure process in PFC3D, the SRM’s strength, elastic modulus and crack growth were obtained. The influence of rock ratios on the SRM’s strength, deformation and failure processes, as well as its internal mesoscale mechanism, were analyzed. By comparing simulation results with experimental data, it was verified that the 3D PFC models were in good agreement with SRM’s real structure and the SRM’s compression process, deformation and failure patterns; its intrinsic mesomechanism can be effectively analyzed based on such 3D PFC models.